Tunable filter imaging of high-redshift quasar fields - Swinbank, J; Baker, J; Barr, J; Hook, I; Bland-Hawthorn, J (2012)
We have used the Taurus Tunable Filter to search for Lyα emitters in the fields of three high-redshift quasars: two at z∼ 2.2 (MRC B1256-243 and MRC B2158-206) and one at z∼ 4.5 (BR B0019-1522). Our observations had a field of view of around 35arcmin 2, and reached AB magnitudes of ∼21 (MRC B1256-243), ∼22 (MRC B2158-206) and ∼22.6 (BR B0019-1522) depending on wavelength. We have identified candidate emission-line galaxies in all the three fields, with the higher redshift field being by far the richest. By combining our observations with simulations of the instrumental response, we estimate the total density of emission-line galaxies in each field. 17 candidate emission-line galaxies were found within 1.5Mpc of BR B0019-1522, a number density of (4.9 ± 1.2) × 10 -3Mpc -3, suggesting a significant galaxy overdensity at z∼ 4.5. © 2012 The Authors Monthly Notices of the Royal Astronomical Society © 2012 RAS.